Synthesis and characterization of calcium double perovskites for the potential application of semiconducting CO2 sensors. Issue 21 (1st November 2021) - Wang, Guangwei; Mulmi, Suresh; Thangadurai, Venkataraman
Abstract: A conventional solid-state sintering method was used to prepare double perovskite structured compounds BCN (Ba2 Ca0.67 Nb1.33 O6 ), BCNCo (Ba2 Ca0.67 Nb1.33-x Cox O6-δ ) and BCNCoFe (Ba2 Ca0.67 Nb0.67 Co0.66-y Fey O6-δ ), which exhibit significant chemical stability in nitrogen, air, and 2 % CO2 (balanced by nitrogen). SEM images show that the Co dopant causes a dense microstructure for BCNCo compounds. In contrast, the introduction of Fe tends to produce a porous and web-like microstructure for the BCNCoFe series. Ba2 Ca0.67 Nb0.67 Co0.66 O6-δ has a reasonable response (recovery) time at 750 °C and it seems suitable for CO2 detection at elevated temperatures. Among the BCNCoFe compounds, Ba2 Ca0.67 Nb0.67 Co0.33 Fe0.33 O6-δ has the largest capacitance as the CO2 concentration changes from 0 to 2000 ppm, and it exhibits satisfactory sensitivity and repeatability in the temperature range of 450–700 °C with an extra voltage of 0.1 V. To further consider the Ba2 Ca0.67 Nb0.67 Co0.33 Fe0.33 O6-δ compound for CO2 sensing, a sol-gel method was utilized. The sol-gel-prepared Ba2 Ca0.67 Nb0.67 Co0.33 Fe0.33 O6-δ senses CO2 well, and its concentration changes from 0 to 2000 ppm (or from 0 to 300 ppm) in the temperature range of 400–600 °C. The different CO2 sensing properties of all prepared double perovskite compounds can be interpreted by the different surface areas that play critical roles in the chemical adsorption of related gaseous species.